2013 IEEE International Conference on Robotics and Automation 2013
DOI: 10.1109/icra.2013.6630770
|View full text |Cite
|
Sign up to set email alerts
|

Computing with a muscular-hydrostat system

Abstract: Octopus arms, as well as elephant trunks, squid tentacles, and vertebrate tongues are termed muscularhydrostats. In such structures, the volume of the organ remains constant during their motions, enabling diverse, complex, and highly controlled movements without the support of a skeleton. Such flexible structures show major advantages over articulated arms that have a rigid skeleton and joints. These advantages have been attracting roboticists aiming to apply these material properties to soft robot controls. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…The parameters f 1 , f 2 , and f 3 are set to 2.11, 3.73, and 4.33, respectively. Similar inputs were adopted in Hauser et al (2011), Sumioka et al (2011), and Nakajima et al (2013). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters f 1 , f 2 , and f 3 are set to 2.11, 3.73, and 4.33, respectively. Similar inputs were adopted in Hauser et al (2011), Sumioka et al (2011), and Nakajima et al (2013). …”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the body of the octopus arm is highly involved in the production of movements. Accordingly, in robotics, there have been several attempts to characterize the role of the muscular-hydrostat system in terms of its anatomical structure (Mazzolai et al, 2007; Laschi et al, 2009, 2012; Vavourakis et al, 2012a,b) and functionality (Nakajima et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works on morphological computational aspects for soft bodies [13]- [20] has shown that the mechanical properties of such infinite-dimensional bodies can be exploited as real-time computational assets. This approach is related to the reservoir computing framework [21]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…In one case, a simple model of a human musculoskeletal system was used to identify the capacity of computation [9]. In a more biologically plausible example, the computational capacity of a muscular-hydrostat system was investigated and found to have a characteristic memory capacity [10]. In addition, such a system has been demonstrated to have the potential to emulate complex nonlinear dynamical systems, and closed-loop controls [11].…”
Section: Introductionmentioning
confidence: 99%